Degradation of Blue KN-R Dye in Batik Effluent by an Advanced Oxidation Process Using a Combination of Ozonation and Hydrodynamic Cavitation - Eva Fathul Karamah; Pristi Amalia Nurcahyani (Indonesian Journal of Chemistry, 2019)
The popularity of batik has been increasing since it was declared as a world cultural heritage by UNESCO in 2009. Correspondingly, the content of textile dyes in textile industry wastewater is also increased. These dyes contain functional groups which make them quite stable in the environment and causes pollution. In this work, degradation of 100 ppm Blue KN-R has been investigated using ozonation, hydrodynamic cavitation, and a combination of the two for 60 min. The three configuration methods were optimized in terms of different operating parameters, namely flowrate, initial pH and dosage of ozone, to obtain the maximum degradation of Blue KN-R. It was found that the highest decolorization level for a single method was 70.16% for the single ozonation process at pH 11 and 156.48 mg/h of ozone and 1.79% for the single hydrodynamic cavitation process at pH 4. The highest decolorization level was 79.39%, achieved by the combination at pH 11 and 156.48 mg/h of ozone. The mineralization level in the form of a percentage of Total Organic Carbon (TOC) removal by ozonation, hydrodynamic cavitation, and their combination was 14.81, 1.85, and 19.9%, respectively. Due to its better performance, degradation of Blue KN-R was conducted by the hybrid method for 120 min, resulting in 92.63% of decolorization and 24.54% of TOC removal. The degree of synergetic decolorization and mineralization was due to the mechanical and chemical effect of hydrodynamic cavitation in increasing ozone solubility and production of hydroxyl radicals. Degradation of batik effluent has been investigated in optimum conditions for 120 min. The color, COD, BOD, and TSS removal were 67.96, 68.72, 66.54, and 79.84%, respectively.